Aerogel anti-condensation coating and preparation method thereof

By using nano-level aerogel and other components in anti-condensation coatings, the problems of weak bonding, high thick coating cost and short working time of existing coatings are solved, and strong bonding and thin coating are achieved. and long-term anti-condensation effect reduces cost and improves the durability of the paint.

CN119391248AInactive Publication Date: 2025-02-07杭州荣的科创有限公司
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411628794.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing anti-condensing coatings have problems such as weak bonding, high thick coating cost, and short working time, making it difficult to achieve strong bonding, thin coating and long-term anti-condensing effect.

Method used

Using aerogel as the core component, the particle size reaches the nanoscale through pretreatment, and combining binders, dispersants, defoamers, leveling agents, silicon acrylic emulsions, thermal insulation materials and film forming additives to prepare A kind of aerogel anti-condensation coating is produced. The coating is uniformly mixed with each component by ultrasonic dispersion technology to form a coating with high efficiency insulating and strong bonding properties.

Benefits of technology

It realizes the strong adhesion of the paint, thin coating and long-term anti-condensation effect, reduces the material usage and construction cost, improves the durability and stability of the paint, and reduces the frequency of maintenance and re-painting.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of building coatings, in particular to an aerogel anti-condensation coating and a preparation method thereof, and particularly relates to an anti-condensation coating which is high in binding power, capable of being thinly coated and long in effect and a preparation method of the anti-condensation coating. Comprising the following components: 15-50 parts of aerogel, 10-20 parts of a binder, 0.2-1 part of a dispersant, 0.2-2 parts of a defoaming agent, 0.5-5 parts of a leveling agent, 10-50 parts of a silicone acrylic emulsion, 15-50 parts of a thermal insulation material, 2-16 parts of a coalescing agent and 10-30 parts of deionized water. The aerogel has stable physical and chemical properties, and the porous structure of the aerogel can continuously block the temperature and is not easy to form moisture condensation. Meanwhile, the components of the coating are reasonably matched, and all the components have a synergistic effect, so that the coating can keep a good anti-condensation effect in the long-term use process, the frequency of maintenance and re-brushing is reduced, a metal base material is protected from being easily rusted, and the cost and time are saved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of architectural coatings, and specifically to an aerogel anti-condensation coating and a preparation method thereof, and more particularly to an anti-condensation coating with strong adhesion, thin coating and long-lasting effect and a preparation method thereof. Background Art

[0002] During the rainy season or in rainy and humid areas, the air humidity is high, and condensation is prone to occur on surfaces such as walls. Condensation not only affects the appearance, but also affects the safety and service life of buildings and equipment, and provides conditions for the growth of microorganisms, which is harmful to human health. The current methods to prevent condensation mainly include equipment or house structure design and the use of anti-condensation coatings. Structural design is expensive and the construction is complicated, and anti-condensation coatings have become a development trend. Among the existing anti-condensation coatings, one type of coating with air permeability and water absorption is easy to absorb water saturation, the anti-condensation effect time is short, and the coating absorbs water and expands, which will reduce the adhesion; the other anti-condensation coating based on thermal insulation materials needs to be thickly coated (7mm and above) to achieve the anti-condensation effect, which is costly. Therefore, it is an urgent problem to achieve an anti-condensation coating with strong adhesion, thin coating, and long-lasting effect.

[0003] In view of this, the present application provides an aerogel anti-condensation coating and a preparation method thereof. Summary of the invention

[0004] The purpose of the present invention is to provide an aerogel anti-condensation coating and a preparation method thereof, so as to solve the problems of weak adhesion, high cost of thick coating, short action time and the like of the existing anti-condensation coating, and to achieve the coating having strong adhesion, thin coating and long-lasting anti-condensation effect.

[0005] In order to solve the above technical problems, the following technical solutions are adopted: An aerogel anti-condensation coating comprises the following ingredients: 15-50 parts of aerogel, 10-20 parts of a binder, 0.2-1 parts of a dispersant, 0.2-2 parts of a defoamer, 0.5-5 parts of a leveling agent, 10-50 parts of a silicone-acrylic emulsion, 15-50 parts of a heat-insulating material, 2-16 parts of a film-forming aid, and 10-30 parts of deionized water; The aerogel is pre-treated, including drying and ultra-fine treatment, so that the particle size of the aerogel reaches nanometer level; The adhesive is acrylic resin or epoxy resin; The dispersant is a polycarboxylate dispersant; The defoamer is one or more of mineral oil, silicone and polyether; The leveling agent is a polyacrylate leveling agent; The thermal insulation material is one or a mixture of more than one of hollow glass microspheres, hollow ceramic microspheres, closed-cell expanded perlite, and silica aerogel; The film-forming aid is one of dodecyl alcohol ester, propylene glycol butyl ether, propylene glycol phenyl ether, ethylene glycol butyl ether acetate, and propylene glycol methyl ether acetate, or a mixture of more than one of the above.

[0006] A further improvement based on the technical solution is that the silicone-acrylic emulsion adopts an organosilicon-modified silicone-acrylic emulsion, and the organosilicon-modified silicone-acrylic emulsion is an organosilicon monomer containing unsaturated bonds.

[0007] A further improvement based on the technical solution is that the thermal insulation material is a mixture of hollow glass microspheres and silica aerogel, wherein the amount of the hollow glass microspheres is 5-35 parts, and the amount of the silica aerogel is preferably 10-50 parts.

[0008] A further improvement based on the technical solution is that the silica aerogel used is a silica aerogel paste, which includes aerogel powder, an inorganic filler and a dispersant. The aerogel powder, inorganic filler and dispersant are dispersed in water and mixed at a rotation speed of 1000-1500 rpm for 10-180 min.

[0009] The present application provides another technical solution: a method for preparing an aerogel anti-condensation coating, comprising the following steps: Step 1: pre-treating the aerogel, including drying in a vacuum environment and performing ultra-fine treatment, and then fusing with water to obtain an aerogel paste; Step 2: Weigh each component by weight, first add deionized water and silicone-acrylic emulsion into a reaction kettle, and use a speed of 400-2000 r / min for ultrasonic dispersion for 1-35 min; then add a binder, a dispersant, a defoamer, a leveling agent and a film-forming aid, and use a speed of 400-2000 r / min for ultrasonic dispersion for 1-35 min to obtain a coating base material; Step 3: Add the aerogel paste pretreated in step 1 to the coating base material, and disperse it at a speed of 400-1000 r / min for 5-20 min; finally, add the thermal insulation material, and perform ultrasonic dispersion at a speed of 800-1000 r / min for 5-40 min to obtain the aerogel anti-condensation coating.

[0010] Step 4: Adjust the properties of the coating so that the coating meets the construction requirements.

[0011] A further improvement based on the technical solution is that the aerogel is dried in a vacuum drying oven at 80° C.-120° C. for 2-4 hours.

[0012] A further improvement based on the technical solution is that the particle size of the aerogel reaches 50-100 nanometers after ultrafine treatment.

[0013] A further improvement based on the technical solution is that after the coating base material is prepared and ultrasonically dispersed, stirring treatment is required, and the stirring speed each time is 500-800 rpm and the stirring time is 5-30 minutes.

[0014] A further improvement based on the technical solution is that in step 2 and step 3, the ultrasonic dispersion power is 500-1000W.

[0015] A further improvement based on the technical solution is that the viscosity of the aerogel anti-condensation coating is controlled within 20-30 seconds in a Tu-4 cup viscometer, and the solid content is controlled between 30% and 50%.

[0016] The above technical solution has the following beneficial effects: The aerogel anti-condensation coating of the present invention can reduce the temperature difference between the air and the surface of the object from the root, block the overlap of thermal bridges, prevent the appearance of the condensation critical point, and scientifically control the condensation and condensation phenomena.

[0017] Strong adhesion: The selected adhesive has good adhesion to the aerogel, which can ensure that the coating is firmly attached to the surface of the building or equipment and is not easy to fall off. It can maintain strong adhesion even in a humid environment, thereby improving the durability and reliability of the coating.

[0018] Thin coating: Aerogel's efficient thermal insulation performance and unique structure enable the coating to effectively prevent heat transfer at a relatively thin coating thickness, reduce the temperature difference between the surface and the air, and achieve anti-condensation function. Compared with traditional anti-condensation coatings that require thick coating, the coating of the present invention can greatly save material usage, reduce construction costs, and also reduce the weight burden of the coating on buildings or equipment.

[0019] Long-lasting effect: Aerogel has stable physical and chemical properties, can continuously block temperature, and is not easy to form condensation. At the same time, the coating ingredients are reasonably matched and the various ingredients work together, so that the coating can maintain a good anti-condensation effect during long-term use, reducing the frequency of maintenance and re-painting, saving costs and time. DETAILED DESCRIPTION

[0020] In order to make the purpose, technical scheme and advantages of the present application clearer, the present application is further described in detail below through examples. However, it should be understood that the specific embodiments described herein are only used to explain the present application and are not intended to limit the scope of the present application. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concepts of the present application.

[0021] The aerogel anti-condensation coating mainly includes the following components: - Aerogel 10-50 parts: As the core component, it has extremely low thermal conductivity and high porosity, which can effectively prevent heat transfer and reduce the temperature difference between the surface of the object and the air, thereby reducing the generation of condensation. At the same time, the porous structure of aerogel can continuously block the temperature, further enhancing the anti-condensation effect.

[0022] - 10-20 parts of adhesive: Choose high molecular polymers with good adhesive properties, such as acrylic resin, epoxy resin, etc., to ensure that the paint has strong adhesion to the substrates such as the interior walls, ceilings or equipment surfaces of buildings, prevent the coating from falling off, and improve the durability of the paint.

[0023] - Dispersant 0.2-1 part: used to evenly disperse the aerogel in the coating system, prevent aerogel agglomeration, and ensure the stability and uniformity of the coating. For example, polycarboxylate dispersants can be used.

[0024] - Defoamer 0.2-2 parts: eliminates bubbles generated during the preparation and application of the coating, making the coating surface smooth and flat, and improving the quality and performance of the coating. Common defoamers include mineral oil, silicone, polyether defoamers, etc.

[0025] - 0.5-5 parts of leveling agent: Improve the leveling property of the coating after construction, make the coating surface flatter and smoother, and improve the appearance quality of the coating. Polyacrylate leveling agents can be used.

[0026] - 10-50 parts of silicone acrylic emulsion: The silicone acrylic emulsion is a silicone acrylic emulsion modified with organic silicon. More preferably, the silicone acrylic emulsion modified with organic silicon is a functional emulsion obtained by core-shell polymerization of an organic silicon monomer containing an unsaturated bond, such as methyltrimethoxysilane, vinyltriethoxysilane, etc. and an acrylic monomer. The silicone acrylic emulsion has good water resistance and weather resistance.

[0027] - 15-50 parts of thermal insulation material: The thermal insulation material is a mixture of hollow glass microspheres and silica aerogel, wherein the amount of the hollow glass microspheres is 5-25 parts, and the amount of the silica aerogel is preferably 5-25 parts.

[0028] The silica aerogel used is a silica aerogel paste, which includes aerogel powder, inorganic filler and dispersant. The aerogel powder, inorganic filler and dispersant are dispersed in water and mixed at a rotation speed of 1000-1500 rpm for 10-180 min to prepare the paste.

[0029] In the above-mentioned silica aerogel paste, it is further preferred that the selected aerogel powder is a hydrophobic aerogel, the selected inorganic filler is potassium hexatitanate, and the selected dispersant is an ammonium salt dispersant.

[0030] More preferably, the average particle size of the aerogel powder is 10-50 μm, and the tap density is 0.1-0.2 g / cm 3 The selected inorganic filler potassium hexatitanate can not only increase the tap density of the aerogel aqueous paste, but also the thermal conductivity of potassium hexatitanate will decrease at high temperature, and the thermal insulation performance of the prepared paste will be more stable.

[0031] Preferably, the self-developed aerogel aqueous paste can be well mixed with the resin matrix to solve the problem of poor dispersion of aerogel powder. In addition, the aerogel paste is easy to operate and environmentally friendly, without dust pollution, material feeding difficulties and other problems.

[0032] - 2-16 parts of film-forming aid: the film-forming aid is one or more of dodecyl alcohol ester, propylene glycol butyl ether, propylene glycol phenyl ether, ethylene glycol butyl ether acetate, and propylene glycol methyl ether acetate.

[0033] - 10-30 parts of deionized water; Preparation method of the aerogel anti-condensation coating: Step 1: Pre-treat the aerogel The aerogel is placed in a vacuum environment at a certain temperature for drying to remove moisture and impurities in the pores of the aerogel and improve the performance of the aerogel. The dried aerogel is then subjected to ultra-fine fusion water treatment to make its particle size reach nanometer level, increase the contact area between the aerogel and other components, and improve the dispersibility, thereby obtaining an aerogel paste.

[0034] Step 2: Prepare the coating base Weigh each component by weight, first add deionized water and silicone acrylic emulsion into a reaction kettle, and use a rotation speed of 400-2000 r / min to perform ultrasonic dispersion for 1-35 minutes; then add a binder, a dispersant, a defoamer, a leveling agent and a film-forming aid, and use a rotation speed of 400-2000 r / min to perform ultrasonic dispersion for 1-35 minutes to obtain a coating base material.

[0035] Step 3: Add aerogel and insulation materials The aerogel paste pretreated in step 1 is added to the coating base material, and dispersed at a speed of 400-1000 r / min for 5-20 min; finally, the thermal insulation material is added, and ultrasonic dispersion is performed at a speed of 800-1000 r / min for 5-40 min, and finally the aerogel anti-condensation coating is obtained.

[0036] Step 4: Adjust coating properties According to actual needs, the viscosity, solid content and other properties of the coating are adjusted to meet the construction requirements. The viscosity can be adjusted by adding an appropriate amount of solvent or thickener, and the solid content can be adjusted by controlling the proportion of each component.

[0037] More preferably, the aerogel is dried in a vacuum drying oven at 80° C.-120° C. for 2-4 hours.

[0038] More preferably, the aerogel has a particle size of 50-100 nanometers after ultrafine processing.

[0039] More preferably, after the coating base material is prepared and ultrasonically dispersed, stirring treatment is required, and the stirring speed each time is 500-800 rpm and the stirring time is 5-30 minutes.

[0040] Further preferably, in step 2 and step 3, the ultrasonic dispersion power rate is 500-1000W.

[0041] Further preferably, the viscosity of the aerogel anti-condensation coating is controlled at 20-30 seconds in a Tu-4 cup viscometer, and the solid content is controlled between 30% and 50%.

[0042] In order to better complete the aerogel anti-condensation coating, the following preparations are required.

[0043] 1. Raw material preparation: Prepare raw materials such as aerogel (such as silica aerogel), acrylic resin binder, polycarboxylate dispersant, silicone defoamer, polyacrylate leveling agent, silicone modified silicone acrylic emulsion, deionized water, hollow glass microspheres, silica aerogel, and dodecyl alcohol ester. Ensure that the quality of the raw materials meets the requirements, and the particle size and performance indicators of the aerogel meet the pretreatment requirements.

[0044] 2. Aerogel pretreatment: Place the aerogel in a vacuum drying oven and dry it at a certain temperature (such as 80℃ - 120℃) for 2 - 4 hours. Then use mechanical grinding or air flow crushing to ultrafine the aerogel and melt it to a particle size of 50-100 nanometers.

[0045] 3. Adjust the coating properties: Use a viscometer to measure the viscosity of the coating. According to the construction requirements, when spraying, the viscosity is generally controlled at 20-30 seconds (coating-4 cup viscometer). If the viscosity does not meet the requirements, it can be adjusted by adding an appropriate amount of solvent or thickener. At the same time, the solid content of the coating is controlled between 30% and 50%, which is achieved by adjusting the proportion of each component.

[0046] 4. Coating testing and packaging: The prepared aerogel anti-condensation coating is tested for performance, including anti-condensation performance test (which can be carried out in a test box simulating a humid environment), adhesion test (using the pull-off method, etc.), coating thickness and uniformity test, etc. After passing the test, the coating is packed into a sealed container, and the product name, production date, shelf life and other information are marked.

[0047] Experimental data on the effect of aerogel anti-condensation coating 1. Experimental purpose: To verify the technical advantages of aerogel anti-condensation coating in terms of adhesion, thin coating performance and long-term anti-condensation effect, and to conduct quantitative analysis through specific experimental data.

[0048] 2. Experimental Materials and Equipment 1. Experimental materials: Aerogel anti-condensation coating (homemade, prepared according to the above application formula and method).

[0049] Comparative coating 1 (commercially available common air permeable and water-absorbent anti-condensation coating) Comparative coating 2 (commercially available anti-condensation coating based on thermal insulation materials that requires thick coating) Building base material (such as cement mortar board, size 100cm×100cm×5cm) Petri dishes, distilled water, electronic balance, temperature and humidity sensors, constant temperature and humidity chamber, tensile testing machine, coating thickness gauge, etc.

[0050] Specifically, according to different application formulas, five groups of aerogel anti-condensation coatings were prepared in this embodiment, and the specific ingredient list is shown in Table 1 below.

[0051] Table 1 2. Experimental equipment: Constant temperature and humidity chamber: used to simulate different temperature and humidity environments, with a set temperature range of 10℃ - 35℃ and a humidity range of 40% - 95%RH.

[0052] Tensile testing machine: used to test the adhesion between the coating and the substrate, the test speed is 5mm / min.

[0053] Coating thickness gauge: measures the thickness of paint coating with an accuracy of 0.1μm.

[0054] Temperature and humidity sensor: real-time monitoring of ambient temperature and humidity as well as temperature and humidity near the coating surface.

[0055] Electronic balance: with an accuracy of 0.01g, used to measure the amount of condensation water.

[0056] 3. Experimental methods and steps 1. Coating preparation: Aerogel anti-condensation coating, comparative coating 1 and comparative coating 2 were respectively applied on three identical cement mortar boards.

[0057] Aerogel anti-condensation coating is applied in a thin coating method, and the coating thickness is controlled to be 1mm.

[0058] Comparative coating 1 was applied at a conventional thickness of about 5 mm as required by its product instructions.

[0059] Comparative coating 2 was applied at a thickness required to achieve an anti-condensation effect, which was approximately 8 mm.

[0060] After painting, allow to dry naturally at room temperature for 7 days.

[0061] 2. Adhesion test: The adhesion between the three coatings and the substrate was tested using a tensile testing machine.

[0062] Five different locations were selected on each coated plate to make circular bonding specimens with a diameter of 10 mm.

[0063] Fix the clamps of the tensile testing machine on the coating and substrate of the specimen respectively, stretch it at a speed of 5mm / min, record the maximum tensile force value when the specimen is destroyed, and calculate the bonding force according to the formula: Adhesion force (MPa) = maximum tensile force (N) / bonding area (mm²) 3. Thin coating performance test: The panels painted with the three types of coatings were placed in a constant temperature and humidity chamber, and the ambient temperature was set at 25°C and the relative humidity was set at 85%RH.

[0064] Observe the condensation on the coating surface every hour and record the time when condensation begins to appear.

[0065] The temperature and humidity changes near the coating surface are monitored by temperature and humidity sensors.

[0066] Use a coating thickness gauge to measure the coating thickness at different locations, calculate the average thickness, and compare it with the set coating thickness to evaluate the uniformity of the coating thickness.

[0067] 4. Long-term anti-condensation effect test: The three types of coated plates were placed in a constant temperature and humidity chamber, with the water temperature set at 5 degrees, the ambient temperature at about 20 degrees, and the coating within 4mm, and the condensation condition was tested after 1 hour.

[0068] Specifically, an ice-water mixture was placed in the test cup, the temperature was adjusted to 5-7°C, the cup was covered, the laboratory temperature was maintained at 20-25°C, and condensation was observed after 240 minutes of experiment.

[0069] IV. Experimental Data Recording and Analysis 1. Adhesion test data: as shown in Table 2 below.

[0070] Table 2 Analysis: The adhesion of the aerogel anti-condensation coating is significantly higher than that of the comparative coating 1, and it also has a great advantage over the comparative coating 2. This shows that the adhesion between the aerogel anti-condensation coating and the substrate is stronger, and it can better adhere to the building surface, reduce the risk of coating shedding, and improve the durability of the coating.

[0071] 2. Thin coating performance test data is shown in Table 3 below.

[0072] Table 3 Analysis: The aerogel anti-condensation coating has a small thickness deviation and good coating uniformity at the set thin coating thickness (1mm). The condensation start time is more than 6 hours, which is much later than the 2.5 hours of the comparative coating 1, indicating that the aerogel anti-condensation coating can still effectively delay the formation of condensation at a thinner coating thickness. Although the condensation start time of the comparative coating 2 is 4.5 hours when thickly coated, the aerogel anti-condensation coating achieves a longer anti-condensation effect with a thinner coating, reflecting its superior thin coating performance, which can save materials and reduce construction costs.

[0073] 3. The test data of long-term anti-condensation effect is shown in Table 4 below.

[0074] Table 4 Paint Type 240 minutes condensation water volume (g) Changes in coating appearance Example 1 Coating none No significant changes Example 2 Coating none No significant changes Example 3 Coating none No significant changes Example 4 Coating none No significant changes Example 5 Coating none No significant changes Comparative coating 1 2.5-3.2 Local blistering of coating Comparison paint 2 1.0-1.3 No significant changes Analysis: In the 240-minute long-term test, the aerogel anti-condensation coating had no condensation water, and the coating surface did not show obvious changes. The condensation water of coating 1 was 2.5~3.2 grams, and the coating surface had local blistering. The condensation water of coating 2 was 1.0~1.3 grams, and the coating surface did not show obvious changes. The comparative experiment shows that the aerogel anti-condensation coating has a good and long-lasting anti-condensation effect. At the same time, the appearance of the aerogel anti-condensation coating did not change significantly, and the comparison of the condensation effects of coating 1 and coating 2 further proved the stability and durability of the aerogel anti-condensation coating.

[0075] 5. Experimental Conclusion From the above experimental data, it can be concluded that aerogel anti-condensation coating has excellent performance in terms of adhesion, thin coating performance and long-term anti-condensation effect. It has strong adhesion and can be firmly attached to the surface of the substrate; it can effectively prevent condensation in the case of thin coating (1-1.5mm), and the coating has good uniformity; it has a long-term anti-condensation effect, there is no condensation water in the 240-minute test, and the coating appearance remains stable. Compared with ordinary anti-condensation coatings on the market and anti-condensation coatings that require thick coating, aerogel anti-condensation coatings have obvious technical advantages and provide an effective solution to the condensation problem in humid environments.

[0076] The technical advantages of aerogel anti-condensation coatings are mainly reflected in the following aspects: Excellent thermal insulation performance and low thermal conductivity: Aerogel is a material with a nanoporous network structure. Its internal porosity is extremely high, and the movement of gas in the pores is restricted, making heat transfer extremely difficult. Therefore, aerogel anti-condensation coatings have a very low thermal conductivity, which can effectively reduce heat transfer and prevent excessive heat exchange between the surface of buildings or equipment and the surrounding environment. This can keep the surface temperature of the object relatively high, making it difficult to drop below the dew point temperature, thereby avoiding the occurrence of condensation.

[0077] Good thermal insulation effect: In winter or low temperature environments, aerogel anti-condensation coatings can also reduce the loss of heat inside the building, play a good thermal insulation role, and reduce energy consumption; in summer or high temperature environments, it can prevent external heat from entering the room, keep the room cool, reduce the use of air conditioning and other refrigeration equipment, and achieve energy saving.

[0078] Good hydrophobicity: Aerogel materials have hydrophobic properties, which makes aerogel anti-condensation coatings also have excellent hydrophobic properties. Even in a high humidity environment, moisture is not easy to adhere to the surface of the coating, and can quickly slide off or evaporate, thus avoiding the condensation problem caused by moisture accumulation. In addition, the hydrophobic property can also prevent the performance of the coating from deteriorating due to moisture absorption, ensuring the long-term effectiveness and stability of the coating.

[0079] Strong bonding: The binder in the aerogel anti-condensation coating can form a strong bond with the base material of the building or equipment, ensuring that the coating is not easy to fall off or peel. This is very important for buildings and equipment that are exposed to various environmental conditions for a long time, which can ensure the durability of the anti-condensation effect and reduce the cost of maintenance and repair.

[0080] Good performance with thin coating: Compared with some traditional anti-condensation materials that require thicker coatings to achieve better results, aerogel anti-condensation coatings can exert good anti-condensation performance at a thinner coating thickness. This can not only save the amount of coating used and reduce costs, but also reduce the additional burden of the coating on buildings or equipment, and avoid affecting their appearance and structure due to excessively thick coatings.

[0081] Long-term anti-condensation: The performance of aerogel anti-condensation coating is stable and not easily affected by environmental factors. During long-term use, it can continuously and effectively prevent the occurrence of condensation, and reduce equipment damage, product mildew or rust caused by condensation.

[0082] Easy construction: Aerogel anti-condensation coating can be applied by spraying, brushing, roller coating and other construction methods, and is suitable for buildings or equipment surfaces of different shapes and structures. In addition, its construction process is simple and fast, does not require complex construction equipment and technology, can greatly shorten the construction period and improve construction efficiency3.

[0083] Good environmental protection: Aerogel anti-condensation coating uses water as solvent, does not contain volatile harmful substances such as organic solvents, and is harmless to the environment and human health. At the same time, aerogel material itself is an environmentally friendly material that can be recycled and meets the requirements of modern society for environmentally friendly materials.

[0084] Strong weather resistance: Aerogel anti-condensation coating has good weather resistance and can maintain stable performance under different climatic conditions, such as high temperature resistance, low temperature resistance, UV resistance, etc. Whether in the hot southern region or the cold northern region, it can effectively play an anti-condensation role.

[0085] The above is only a preferred specific implementation manner of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can make equivalent substitutions or changes within the technical scope disclosed in the present application according to the technical solution and application concept of the present application, which should be covered by the protection scope of the present application.

Claims

1. An aerogel anti-condensation coating, characterized in that: The invention comprises the following ingredients: 15-50 parts of aerogel, 10-20 parts of binder, 0.2-1 parts of dispersant, 0.2-2 parts of defoamer, 0.5-5 parts of leveling agent, 10-50 parts of silicone-acrylic emulsion, 15-50 parts of thermal insulation material, 2-16 parts of film-forming aid and 10-30 parts of deionized water; The aerogel is pre-treated, including drying and ultra-fine treatment, so that the particle size of the aerogel reaches nanometer level; The adhesive is acrylic resin or epoxy resin; The dispersant is a polycarboxylate dispersant; The defoamer is one or more of mineral oil, silicone and polyether; The leveling agent is a polyacrylate leveling agent; The thermal insulation material is one or a mixture of more than one of hollow glass microspheres, hollow ceramic microspheres, closed-cell expanded perlite, and silica aerogel; The film-forming aid is one of dodecyl alcohol ester, propylene glycol butyl ether, propylene glycol phenyl ether, ethylene glycol butyl ether acetate, and propylene glycol methyl ether acetate, or a mixture of more than one of the above.

2. The aerogel anti-condensation coating according to claim 1, characterized in that: The silicone-acrylic emulsion adopts organosilicon-modified silicone-acrylic emulsion, and the organosilicon-modified silicone-acrylic emulsion is an organosilicon monomer containing unsaturated bonds.

3. The aerogel anti-condensation coating according to claim 1, characterized in that: The heat insulating material is a mixture of hollow glass microspheres and silica aerogel, wherein the amount of the hollow glass microspheres is 5-35 parts, and the amount of the silica aerogel is 10-50 parts.

4. The aerogel anti-condensation coating according to claim 1, characterized in that: The silica aerogel used is a silica aerogel paste, which includes aerogel powder, inorganic filler and dispersant. The aerogel powder, inorganic filler and dispersant are dispersed in water and mixed at a rotation speed of 1000-1500 rpm for 10-180 min to prepare the paste.

5. A method for preparing an aerogel anti-condensation coating, characterized in that: The following steps are involved: Step 1: pre-treating the aerogel, including drying in a vacuum environment and performing ultra-fine treatment, and then fusing with water to obtain an aerogel paste; Step 2: Weigh each component by weight, first add deionized water and silicone-acrylic emulsion into a reaction kettle, and use a speed of 400-2000 r / min for ultrasonic dispersion for 1-35 min; then add a binder, a dispersant, a defoamer, a leveling agent and a film-forming aid, and use a speed of 400-2000 r / min for ultrasonic dispersion for 1-35 min to obtain a coating base material; Step 3: adding the aerogel paste pretreated in step 1 to the coating base material, and dispersing it at a speed of 400-1000 r / min for 5-20 min; finally, adding the thermal insulation material, and performing ultrasonic dispersion at a speed of 800-1000 r / min for 5-40 min, and finally obtaining the aerogel anti-condensation coating; Step 4: Adjust the performance of the coating so that the aerogel anti-condensation coating meets the construction requirements.

6. The method for preparing the aerogel anti-condensation coating according to claim 5, characterized in that: The aerogel is dried in a vacuum drying oven at 80° C.-120° C. for 2-4 hours.

7. The method for preparing the aerogel anti-condensation coating according to claim 5, characterized in that: After the aerogel is ultra-finely treated, the particle size reaches 50-100 nanometers.

8. The method for preparing the aerogel anti-condensation coating according to claim 5, characterized in that: After the coating base material is prepared and ultrasonically dispersed, stirring treatment is required, and the stirring speed is 500-800 rpm each time, and the stirring time is 5-30 minutes.

9. The method for preparing the aerogel anti-condensation coating according to claim 5, characterized in that: In step 2 and step 3, the ultrasonic dispersion power is 500-1000W.

10. The method for preparing the aerogel anti-dew condensation coating according to claim 5, characterized in that: The viscosity of the aerogel anti-condensation coating is controlled at 20-30 seconds in a Tu-4 cup viscometer, and the solid content is controlled between 30% and 50%.

Citation Information

Cited By

  • Difunctional anti-condensation coating and preparation method thereof

    CN122356911A